АЛБАН БУС УЛС ТӨР: КЛИЕНТЕЛИЗМ, ТӨР БОЛОН НАМЫГ БАРЬЦААЛАХ ТУХАЙ ОЙЛГОЛТЫГ ТАЙЛБАРЛАХ НЬ - Д.Бадамдаш; Б.Сарантуяа; Д. Бумдарь (Politology, 2024)
This article aims to elucidate the distinct political development in post-communist countries after 1989, focusing on the deviations from democratic governance. Drawing upon the insightful analysis provided by Czech political scientist Michal Klima in his work titled "Informal Politics in Post-Communist Europe: Political Parties, Clientelism and State Capture", this review article aims to synthesize and present key findings related to clientelism, the challenges of countering the state, and the strategies employed in managing the state. The analysis encompasses elements such as clientelism, corruption, and the patronage system, highlighting the nuanced perspectives on these issues within the framework of the post-communist political landscape. The overarching goal is to contribute to a comprehensive understanding of the post communist political dynamics, encompassing diverse elements such as clientelism, state governance, and the intricate interplay of political forces. In conclusion, the analysis serves as a precursor to further exploration and understanding of the post-communist political landscape, offering valuable insights into the complex nature of state governance, clientelism, and other challenges to revive the civil society to counter these defective elements of the democratic regime. Хураангуй: Энэхүү өгүүллээр 1989 оноос хойших үеийн коммунизмаас ардчилсан тогтолцоонд шилжсэн орнуудын улс төрийн хөгжлийг ойлгоход нэн чухал ач холбогдолтой улс төрийн нам-эдийн засгийн албан бус хамаарлын тухай шинэ өнцгийг өгүүлж далд сүлжээ, далд улс төрийн бүтэц бүхий клиентелизм, авлига, патрон ёсны тухай ойлголтыг улс төрийн намын судлагдахуунд нэгтгэх зорилго бүхий албан бус сүлжээ, албан бус солилцоо, албан бус улс төр, албан бус пост-коммунист номенклатур1, албан бус намын хувьчлал ба колоничлол, албан бус “үйлчлүүлэгч-үйлчлүүлэгчийн” загвар, далд улс төрийн урсгал, далд хэлбэрээр нам, төрийг барьцаалах зэрэг нэр томьёог ашиглаж тайлбарласан Чехийн улс төр судлаач Михал Климагийн “Пост-Коммунист Европ дахь албан бус улс төр: улс төрийн нам, клиентелизм ба төрийг барьцаалах” номд анализ хийж дээрх хэсэгт өгүүлсэн нэр томьёоны тайлбарыг нэгтгэн хүргүүлэхийн чацуу “клиентлизм, намыг барьцаалах болон төрийг барьцаалах” гэх ойлголтуудыг тодорхойлон дүгнэхэд төвлөрч дүгнэлт хэсгээр дамжуулан Михал Климагийн бүтээлд анализ хийснээ танилцуулах болно.